The Problems of International Civil Law of Indonesia in Protecting Transnational E-Commerce Consumers - Musleh Herry; Meisy Fajarani (Fakultas Hukum Universitas Mataram, 2022)
Technological advances on a transnational scale have had a considerable impact on all levels of Indonesian society. One of the technological advances is the existence of gadgets. Not only positive effects, but they also bring negative impacts. Furthermore, the existence of gadgets continues to grow with more transactions being carried out. Unfortunately, this can be a dispute. The purpose of this research is to propose the problems of Indonesian International Civil Law which have not regulated and provided guarantees to protect transnational e-Commerce interests and their solutions. The method used in this research is normative with a statutory and conceptual approach. The results of this study are the existence of Consumer Protection Law (UUPK), Electronic Information and Transactions Law (ITE Law), Money Supply Law (UUUP), and International Civil Law (HPI) of Indonesia have not provided a clear guarantee of protection related to the choice of law in transnational scale e-commerce contracts. Besides, they also have not been able to accommodate the interests of consumers. One of the solutions offered is concretizing the principle of the recipient country. It is a rule that allows end-users to apply the Consumer Protection Law of their country. This principle is excluded from consumer transactions. This also does not apply .e-commerce contracts. This principle is taken from the Rome and Brussels Convention which is incorporated into the Directive, namely the Law for the EEC community (Europe Union). To provide legal guarantees for consumers, thus the interests’s of consumers can be protected.